Exploring Knowledge Development for Sustaining the Intellectual Capital of Technical and Vocational Education and Training leadership Research: A Qualitative Study At a Global South University - Ferdinand-James, Debra; Nelson, Karlene; Bishop, Natalie (International Journal of Education and Teaching Zone, 2024)
A Caribbean University in the Global South is committed to sustaining Technical and Vocational Education and Training (TVET) "Leadership" research as it remains a crucial driver for leading social and economic transformation in the aftermath of the COVID-19 global pandemic. This exploratory study aims to examine the extent to which a“TVET Leadership'' focus exists in research titles of final projects/theses from this University’s Leadership in TVET and Workforce Development graduate programs and explore directions for future knowledge development. Using content analysis, these final research projects/theses’ titles were thematically categorized that revealed a lot more emphasis on such themes as TVET stakeholder perceptions, pedagogy, and youth participation than “Leadership.” These findings will resonate with local “TVET” research supervisors and supervisees in the Global South at a premiere Caribbean university in knowing what research has been done in their chosen field in avoiding duplication of efforts and knowing what remains to be researched. The study findings will also contribute to the limited scholarly literature from the Caribbean in the Global South on knowledge development in TVET “Leadership” research.